(untitled) (Raparin Journal of Humanities (RJH), 2025)
With a rapid change of Kurdistan Region’s socio-economic life following 2003, the English language has quickly emerged as the new must-have language for this millennium. This article explores the way teaching of English as a foreign language has become popular in the past two decades and how the large influx of international expats has brought different cultures and languages into the workplace and society, especially in Erbil city. This study investigates the use of the English language as a lingua franca in Erbil, and it has therefore chosen the golden zone as a typical area in Erbil where there is a high density of international people for whom English is a means of communication when they interact with speakers of other languages. This study follows the research methods of linguistic landscape (LL), which tackle the coexistence of English with local languages (e.g. Edelman, 2006; Cenoz & Gorter, 2006; Backhaus, 2007). However, there is very few research on how English interacts with other languages in multilingual destinations in the expanding circle. To investigate this further, three locations are selected (a café/restaurant, a real estate agency, and a barber shop). The owners of these venues are invited to participate in one-on-one in-depth interviews. Findings indicate that there are three categories of population in the Golden Zone in Erbil which can be classified as people who speak only English, people who speak Kurdish, Arabic, and English, and people who speak Arabic and English. The responses from the three interviewee groups indicate that when these three categories of people meet, it is inevitable that English will be used as a lingua franca for ease of communication.